Dukungan Keluarga Terhadap Kepatuhan Minum Obat Pasien Hipertensi Di Puskesmas Mirit - Yuda, Hendri Tamara; Al Falaq, Farid; Santoso, Eko Budi (Borobudur Nursing Review, 2024)
Hypertension is a higher than normal blood pressure where the systole pressure is ≥140 mmHg and the diastole pressure is ≥90 mmHg. One way to control hypertension is to consume antihypertensive drugs as recommended by health workers. Familysupport greatly affects the patient's adherence to taking the drug. This study aims to find out whether there is a relationship between family support for adherence to taking medications for hypertensive patients at the Mirit health center. This study uses quantitative correlation method with cross sectonal approach. This sample using 60 respondents was taken by purposive sampling. Data collection using questionnaires was then analyzed descriptively and correlationally using the Spearman Rank test. The results of the study were mostly moderate family support (41.7%) Most had moderate compliance rates (58.3%). The results of data analysis using the Spearman Rank test, obtained a relationship of family support for adherence to taking p-value drugs 0.00 < (0.05). The results showed that there was a relationship between family support for taking medicine adherence